(untitled) (Quinto Sol, 2025)
In the last quarter of the 19th century, commemorative practices served as a tool for consolidating Argentine national identity and strengthening the distinct identities of immigrant groups settled in the country. The leaders of the Italian community established in the city of Corrientes strove for the construction of Italian identity, especially after the unification of the peninsula was completed in 1870. With this in mind, they organized events that honored their national heroes, Giuseppe Mazzini and Giuseppe Garibaldi, while also providing a space for the expression of Italian and Argentine brotherhood. This article studies the commemorative activities of Italians in the city of Corrientes and analyzes the special treatment Garibaldi received due to his participation in the River Plate civil wars, within the framework of the Corrientes provincial leadership’s confrontation with Juan Manuel de Rosas. The enthusiasm aroused by the memory of the Italian politician, fostered by the leaders of the community and supported by that leadership, is explained by the fact that his figure responded to the aspirations of the Corrientes urban elite to highlight the role of the province in shaping the Argentine nation based on its past resistance to the Rosas government.